Manejo agronómico del cultivo de cebolla puerro (Allium porrum) en el Ecuador - Carriel García, Neyvi Valeria (2023)
In Ecuador, the leek onion crop is gaining great importance among vegetables, due to its wide consumption for its physical appearance and flavor similar to white onion; it has agroeconomic characteristics that make it important in the national and international context, with high production volumes in small areas, nutritional value, employment generation in the field and in agribusiness. For the preparation of the document, information was gathered from updated texts, virtual libraries, magazines, web pages and scientific articles that contributed to the development of the research on the agronomic management of the leek onion crop (A. porrum) in Ecuador. From the above detailed, it was determined that the minimum temperature for germination is 5 ℃, the optimum temperature is 20 - 26 ℃ and the maximum temperature is 36. Photoperiod is a limiting factor for leek growth, because the plant only grows properly if the day length is 10 to 12 hours or more than 14 hours. Leek onion adapts well to deep, cool soils rich in organic matter; it is not suitable for soils that are too alkaline, nor for soils with acidity, as it is a sensitive crop and tolerates an acidity limit around pH 6. The agronomic management of the leek onion crop involves different agricultural activities, taking into account the following tasks: seedbeds, soil preparation, sowing, irrigation, topping, blanching, fertilization, weed control, pest control and harvesting. Within the nutrition of the leek onion crop, nitrogen is highly required, as well as potassium, which is very important for root development and leaf formation.